Analisis Manajemen Tata Kelola Pasar Rakyat Di Pasar Kranggot Kota Cilegon - Yulianti, Wahdiyatun; Handayani, Riny (Jurnal PubBis, 2025)
Development is a fundamental thing as well as a benchmark in the improvement of an area. The market is one of the facilities for fulfilling daily needs and has an important role in people's lives. The importance of market development is due to the increasing needs of the community and the market has become the main pillar of the economy in an area. Cilegon City Kranggot Market is the main center of economic activity in Ciegon City which is also managed by the Regional Government, however, the management of Cilegon Kranggot Market is considered not optimal because there are still many problems that occur. This research uses a qualitative method with a descriptive approach. This research focuses on the Management Analysis of People's Market Governance in Kranggot Market, Cilegon City. The data sources in this study come from primary data and secondary data. This research uses data collection techniques in the form of interviews with 13 informants, field observations, and documentation studies. The results of this study indicate that overall the governance management carried out for the Cilegon City Kranggot Market has been carried out but not yet optimal, this is based on continuous planning factors, lack of supervision, and the condition of the building and market location that needs to be changed as a whole. Not only that, traders are also a factor inhibiting the existence of governance management for Kranggot Market. The implementation of governance management for Kranggot Market needs to be further optimized, especially in terms of planning, basically in a management planning is the main factor that determines the next stage. As well as the implementation of strengthening the supervisory system, to control the governance management process takes place. By applying good management functions, the implementation of governance for the market will result in good and optimal market management and contribute to the region.